Inhibitory Effects of the Lactobacillus rhamnosus GG Effector Protein HM0539 on Inflammatory Response Through the TLR4/MyD88/NF-кB Axis - Li, Yubin; Yang, Shaojie; Lun, Jingxian; Gao, Jie; Gao, Xuefeng; Gong, Zelong; Wan, Yu; He, Xiaolong; Cao, Hong (Frontiers in Immunology, 2020)
Inflammatory bowel disease (IBD) is a chronic recurrent intestinal inflammatory with no effective treatment. It is known that postbiotics have gained widely attention because of their outstanding advantages in intestinal health issues. In previous studies, we characterized a novel Lactobacillus rhamnosus GG (LGG)-derived postbiotic, HM0539, with significant protective effects against the murine colitis, but the precise mechanism is unclear yet. In this study, we hypothesized that the protective function of HM0539 might be derived by the modulation of TLR4/Myd88/NF-κB signaling pathway, critical pathways widely involved in the modulation of inflammatory responses. To test this hypothesis, the underlying anti-inflammatory effects and associated mechanisms of HM0539 were determined both in lipopolysaccharide (LPS)-induced RAW 264.7 macrophages and in dextran sulfate sodium (DSS)-induced murine colitis. However, the results showed that HM0539 suppressed the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) by down-regulating their activation of promoter respectively, and subsequently inhibited the production of nitric oxide (NO) and prostaglandin E2 (PGE2). Meanwhile, we found HM0539 could ultimately modulate the activation of distal NF-κB, as reflected by reducing the activation of TLR4 and suppressing the transduction of MyD88. However, even though the overexpression of TLR4 or MyD88 obviously reversed the effect of HM0539 on LPS-induced inflammation, it still had a certain degree of inhibition. Consistent with these in vitro findings, we found that treatment with HM0539 remarkably inhibited the expression of inflammatory mediators correlated with the suppression of TLR4/Myd88/NF-κB activation in colon tissue. In conclusion, HM0539 proved promising anti-inflammatory potential modulation, at least in part through the down-regulation of TLR4-MyD88 axis as well as downstream MyD88-dependent activated NF-κB signaling, which might play a potential therapeutic option for IBD.